Effect of organic solvents on earwax cortisol extraction in Hanwoo cattle - Mohammad Ataallahi; Geun-Woo Park; Kyu-Hyun Park (Journal of Animal Science and Technology)
Earwax, a semi-solid substance, of both humans and non-human animals contains the stress hormone cortisol. Extraction of cortisol from earwax requires the use of organic solvents to eliminate interference factors. This study aimed to investigate the effects of organic solvents on the extraction efficiency of earwax cortisol from Hanwoo cattle. A factorial arrangement was used to determine the effects of solvent source (methyl alcohol [MA], diethyl ether [DE]) and assay diluent buffer (ADB) (0 and 1 mL) on earwax cortisol concentration (ECC) in Hanwoo cattle (parity 3, body weight = 462 kg). A 25 mg portion of the earwax sample was suspended in ADB, while another 25 mg portion was not suspended prior to extraction with MA and DE. The ECC was measured using a commercial enzyme-linked immunosorbent assay cortisol kit. The results indicated that cortisol can be extracted from earwax with or without ADB. The extraction yield of cortisol from earwax was higher with MA than with DE (p < 0.05). In conclusion, MA is the preferred solvent for cortisol extraction owing to its high extraction yield, simple extraction process, and relatively low solvent consumption. Moreover, earwax cortisol can be used as a biomarker to evaluate the degree of chronic stress in Hanwoo cattle.